Development of a 18F‐Labeled Tetrazine with Favorable Pharmacokinetics for Bioorthogonal PET Imaging1. Issue 36 (2nd July 2014) - Denk, Christoph; Svatunek, Dennis; Filip, Thomas; Wanek, Thomas; Lumpi, Daniel; Fröhlich, Johannes; Kuntner, Claudia; Mikula, Hannes
Abstract A low‐molecular‐weight 18F‐labeled tetrazine derivative was developed as a highly versatile tool for bioorthogonal PET imaging. Prosthetic groups and undesired carrying of 18F through additional steps were evaded by direct 18F‐fluorination of an appropriate tetrazine precursor. Reaction kinetics of the cycloaddition with trans‐cyclooctenes were investigated by applying quantum chemical calculations and stopped‐flow measurements in human plasma; the results indicated that the labeled tetrazine is suitable as a bioorthogonal probe for the imaging of dienophile‐tagged (bio)molecules. In vitro and in vivo investigations revealed high stability and PET/MRI in mice showed fast homogeneous biodistribution of the 18F‐labeled tetrazine that also passes the blood–brain barrier. An in vivo click experiment confirmed the bioorthogonal behavior of this novel tetrazine probe. Due to favorable chemical and pharmacokinetic properties this bioorthogonal agent should find application in bioimaging and biomedical research.